2009
DOI: 10.4067/s0718-19572009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Desarrollo larvario y supervivencia hasta la metamorfosis del erizo Tripneutes ventricosus (Lamarck) (Echinodermata: Echinoidea) alimentado con microalgas a dos temperaturas

Abstract: Abstract.-Larval development and survival of Tripneutes ventricosus up to metamorphosis were evaluated. Ten sexually mature specimens were collected from 'Faro de Charagato' to 'Laja Amarilla' (10º50'07"N, 64º09'33"O) Cubagua island, Nueva Esparta state, Venezuela. Spontaneous spawning of the organisms was produced during their transport to the laboratory. Pluteus larvae (2 ind mL -1 ) were randomly distributed into 16 plastic recipients (18 L) (32000 larvae/recipient), with 16 L of filtered sea water and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Nonetheless, despite the research conducted on the effect of temperature on the development and survival of larvae of marine invertebrates (see Bassim andSammarco 2003, Randall andSzmant 2009), in particular echinoderms (see Johnson and Babcock 1994), little is known about the effects of high temperatures on settlement and onset of metamorphosis. There are reports on larval development of species of a more tropical distribution, such as Tripneustes ventricosus, which properly completes its development at temperatures of up to 29 ºC (see Rosas et al 2009). Chen and Chen (1992) found that larvae of Arachnoides placenta maintained at temperatures ranging from 28 to 34 ºC showed a decrease in percentage of metamorphosed larvae at the end of the experiments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, despite the research conducted on the effect of temperature on the development and survival of larvae of marine invertebrates (see Bassim andSammarco 2003, Randall andSzmant 2009), in particular echinoderms (see Johnson and Babcock 1994), little is known about the effects of high temperatures on settlement and onset of metamorphosis. There are reports on larval development of species of a more tropical distribution, such as Tripneustes ventricosus, which properly completes its development at temperatures of up to 29 ºC (see Rosas et al 2009). Chen and Chen (1992) found that larvae of Arachnoides placenta maintained at temperatures ranging from 28 to 34 ºC showed a decrease in percentage of metamorphosed larvae at the end of the experiments.…”
Section: Introductionmentioning
confidence: 98%
“…A pesar de los estudios realizados acerca del efecto de la temperatura en el desarrollo y la supervivencia de larvas de invertebrados marinos (ver Bassim y Sammarco 2003, Randall y Szmant 2009), en particular los equinodermos (ver Johnson y Babcock 1994), poco se sabe acerca de los efectos de altas temperaturas en el asentamiento y el inicio de la metamorfosis. Se han reportado desarrollos larvarios de especies de distribución más tropical, como Tripneustes ventricosus, que completa adecuadamente su desarrollo a temperaturas de hasta 29 ºC (ver Rosas et al 2009). Chen y Chen (1992) encontraron que las larvas de la galleta de mar Arachnoides placenta mantenidas a un intervalo de temperaturas entre 28 y 34 ºC mostraron una disminución en el porcentaje de larvas metamorfoseadas al final de los experimentos.…”
Section: Introductionunclassified